STUDY OF LITERATURE ABOUT INFLUENCING FACTORS WOMEN OF CHILDBEARING IN IMMUNIZING TETANUS TOXOID (TT) - Mediana Pratiwi, Nor Rimadhanty; Rizani, Ahmad; Daiyah, Isrowiyatun (JURNAL KEBIDANAN BESTARI, 2021)
Background: Tetanus toxoid (TT) immunization for women of reproductive age is a procedure that strengthens the immune system of women aged 15 to 49 years, including pregnant and non-pregnant, to protect them from tetanus infection. While not being immunized against tetanus toxoid (TT) is not life threatening, it can have an effect on tetanus infection control, which is a risk factor for maternal and infant mortality. Methods: This study was a form of qualitative analysis that incorporates research methods and literature reviews. With a significance level of 0.05, data were provided in the form of bivariate and univariate analysis tables. Data was gathered from 10 journals, 7 of which were national and 3 of which were foreign. The population used was women of childbearing age with samples of potential brides and pregnant women. Results: The results of a literature review of 10 publications that tetanus toxoid immunizing action was achieved revealed (71,87%-33,9%), age (99%-6,25%), attitude (83,3%-51%), parity (77,8%-23,4%), and husband's support (82,6%-53,8%). The findings of the statistical tests reveal age (p = 0,009; 0,000), attitude (0,0038; 0,013; 0,001; 0,001; 0,000), parity (p = 0,039; 0,03; AOR = 2.3, 95% CI; 0,277; 1,00), and husband's support (p = 0,018; 0,016; 0,001; 0,111). Conclusion: According to the findings of the literature review, all articles discussing age (100%), attitudes (100%), 3 out of 5 articles about parity (60%), and 3 out of 4 articles about husband's support (67%) stated this was a consideration that affects the vaccination of women of childbearing age against tetanus toxoid (TT). Keywords: Age, Attitude, Parity, Husband Support, Fertile Age Women, Tetanus Toxoid Immunization.